2019
DOI: 10.3390/en12173323
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Structure of Electricity Generation in Poland in View of the EU Climate Package

Abstract: The fuel mix of electricity generation in Poland is currently based predominantly on solid fuels. In addition, the generation power base is outdated. Many of the generating units are inefficient, uneconomic, and do not comply ecological standards, so they should be withdrawn from use in the near future. Poland, which consumes approximately 170 TWh of electricity, needs to determine the direction of the further development of the energy sector. The concepts of covering domestic demand for electricity were outli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…The results of dividing the EU countries into homogeneous structures in terms of the level of emissions for each studied substance showed that in many EU countries, the emissions in relation to the size of the economy characterized by the GDP value are incomparably high. In the case of Poland, the main reason for this is to be found in the energy sector based on conventional energy sources ( Gawlik and Mokrzycki, 2019 ) and in the road transport sector ( National Road Safety Programme, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of dividing the EU countries into homogeneous structures in terms of the level of emissions for each studied substance showed that in many EU countries, the emissions in relation to the size of the economy characterized by the GDP value are incomparably high. In the case of Poland, the main reason for this is to be found in the energy sector based on conventional energy sources ( Gawlik and Mokrzycki, 2019 ) and in the road transport sector ( National Road Safety Programme, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most of the existing hard coal-fired power stations are outdated, low-efficiency units. The age structure of boilers and turbine units used in power plants is extremely variable [6,18], 57% of generating units is over 30 years old, of which as much as 9% is over 40 years old, and new generation units-in operation for fewer than 10 years-account for only 10% [6]. In 2019, the share of coal in electricity production was 73.6% and it was lower by 4.8% compared to 2018.…”
Section: Electricity Production In Polandmentioning
confidence: 99%
“…Most of the existing hard coal-fired power plants are obsolete and low-efficiency units. The age structure of boilers and turbine sets operated in power plants is very variable [5,6]. New generation units-operating for less than 10 years-constitute only 10% of the capacity structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations